1999
DOI: 10.1099/0022-1317-80-6-1347
|View full text |Cite
|
Sign up to set email alerts
|

The nine C-terminal residues of the grapevine fanleaf nepovirus movement protein are critical for systemic virus spread.

Abstract: The grapevine fanleaf virus (GFLV)RNA2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…CP to encapsidate viral RNA was assessed under conditions that allows to distinguish RNase-protected, encapsidated viral RNA (P condition, PIPES buffer) from total, encapsidated, and nonencapsidated viral RNA (T condition, TLES buffer) as described previously (6). As expected, under T condition, progeny viral RNA was detected for all GFLV RNA1 and RNA2 combinations (Fig.…”
Section: Vol 84 2010 Coat Protein Determinants Of Gflv Transmissionmentioning
confidence: 94%
See 2 more Smart Citations
“…CP to encapsidate viral RNA was assessed under conditions that allows to distinguish RNase-protected, encapsidated viral RNA (P condition, PIPES buffer) from total, encapsidated, and nonencapsidated viral RNA (T condition, TLES buffer) as described previously (6). As expected, under T condition, progeny viral RNA was detected for all GFLV RNA1 and RNA2 combinations (Fig.…”
Section: Vol 84 2010 Coat Protein Determinants Of Gflv Transmissionmentioning
confidence: 94%
“…Plasmid pVec2ABC carrying a fulllength cDNA copy of GFLV-F13 RNA2 was used as a template to develop chimeric 2C CP genes (6). For cloning purposes, an Acc65I restriction site was introduced into pVec2ABC from positions 2678 to 2683 (nucleotide positions are given according to the GFLV-F13 RNA2 sequence, GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that in vivo only homologous virions can be moved from cell to cell by the viral transport tubule and that the MP is not able to assist the movement of virions even of related viruses. Little, but supportive, evidence is available for this hypothesis from a study performed by Belin et al (1999) on the nepovirus GFLV, showing that nine C-terminal residues of the 2B movement protein must be of the same virus origin as the 2C coat protein for successful systemic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence for a specific interaction between the C terminus of the CPMV MP and virions was presented by Lekkerkerker et al (1996), who showed that a mutant virus encoding an MP lacking the C-terminal 18 amino acids (residues 313-331) was able to form tubules in protoplasts which did not contain virus particles, and the mutant was not able to spread systemically in plant tissue. Furthermore, for Grapevine fanleaf virus (GFLV), another member of the family Comoviridae, Belin et al (1999) found that the nine C-terminal amino acids of the MP must be of the same virus origin as the CP for successful systemic spread, and they also proposed a requirement for specific interactions between the movement protein (2B MP ) and the coat protein (2C CP ).…”
Section: Introductionmentioning
confidence: 99%